EVALUATION OF WILD SUGARCANE ERIANTHUS ARUNDINACEUS (RETZ) JESW. GERMPLASM - V.A. Amalraj; P. Rakkiyappan; A.K Rema Devi (Journal of Sugarcane Research, 2020)
The wild sugarcane species, Erianthus arundinaceus, was evaluated for its stalk characters, biomass production, fiber content and juice quality. This species has the potential to provide fiber as raw material for paper manufacture, bio-fermentation of juice into alcohol and energy through cogeneration. So far no systematic evaluation of this semi-wild species has been done for biomass yield, fiber content and quality, and no program to cultivate it for its co-products ever attempted. Initially, 107 accessions available in the world germplasm collection of Erianthus maintained at the Sugarcane Breeding Institute, Coimbatore, were screened for nine quantitative traits and the data were subjected to analysis of variance and correlation analysis. Single stalk weight and number of tillers showed high variance (CV%). Hierarchical cluster analysis produced nine clusters. Out of these 107 clones, six clones were further evaluated for 13 yield characters. Analysis of the data indicated that the clone SES 159 was the most promising in terms of biomass and stalk yield.